Laparoscopic uterine fixation and ovarian pexy for fertility and ovarian preservation in a 40-year-old with anal cancer - Victoria Dillard, M.D.; Ameek Bindra, B.A.; Jeitzel Torres-Rodriguez, B.S.; Amy M. Vallerie, M.D.; Marc Fields, M.D.; Sara Ann B. Gilbert, M.D.; Eve Zaritsky, M.D. (F&S Reports)
Objective: To describe a novel multidisciplinary approach to preserve ovarian function and fertility in a 40-year-old woman with newly diagnosed anal cancer. Design: Case study of a multidisciplinary ovarian and fertility preservation strategy. Patient: A 40-year-old nulliparous woman with a newly diagnosed stage IIA squamous cell carcinoma (SCC) of the anal canal and a history of cervical intraepithelial neoplasia (CIN 3, status post LEEP). Exposure: The patient underwent an oocyte retrieval, followed by laparoscopic ovarian and uterine pexy to minimize radiation dose to the ovaries and uterus. She subsequently received external beam radiation therapy (EBRT). Main Outcome Measures: Radiation dose to the ovaries and uterus; preservation of ovarian function and reproductive potential. Results: The estimated mean radiation doses to the ovaries were limited to <500 cGy, cumulatively, potentially preserving ovarian function, whereas without ovarian transposition, the ovaries would have received at least 4,200 cGy, which would have certainly caused premature primary ovarian insufficiency (POI). Additionally, the uterus received a modestly lower dose than it would have without the uterine pexy. This collaborative approach resulted in a decreased likelihood of early menopause, underscoring the importance of centralized and coordinated care. Conclusion: This case study underscores the importance of a multidisciplinary approach involving fertility, gynecology, and radiation oncology departments to ensure an integrated care model focused on preserving fertility and ovarian function. It supports the growing body of evidence that standardized coordination among these specialties is essential and aligns with broader efforts to prioritize fertility preservation in cancer care planning.